Relationships between biotic and abiotic range characteristics and productivity of reindeer husbandry in Sweden - Lundqvist, Henrik; Norell, Lennart; Danell, Öje (Rangifer, 2009)
Reindeer husbandry is a form of pastoralism where vast areas are used as forage ranges throughout the year. The productivity of the reindeer industry in Sweden is affected by a multitude of factors on different geographical and temporal scales. Our aim was to find combinations of factors characterizing the environmental conditions for reindeer husbandry in the 51 herding districts in Sweden, which correlate strongly with variations in productivity both between herding districts in general and between years within districts. Productivities were described by estimated herd growth rates and carcass condition of slaughtered females and calves. These dependent variables were related to the environmental independent variables using linear regression models and structural equation modelling. The independent variables were either considered as stable (e.g. topography, vegetation and infrastructure) or temporally changing (e.g. season lengths, weather events, disturbances and animal slaughter strategies). The most relevant independent variables were included in a cluster analysis to suggest a grouping of herding districts based on similarities in environmental conditions. Considerably larger variation in productivity was found between herding districts than between years. Different variables were found to be important for between-district and within-district variations, respectively. Season lengths and animal densities were found significant at both levels of variation. Other variables found to be relevant were ruggedness, snow condition, harassing insect activity, supplementary feeding, calf slaughter ratio and previousyear animal condition. Snow precipitation, ice-crust formation and forage quality were presumed to be relevant for reindeer productivity, but were not found to have a large impact on productivity. These factors, however, may have been counteracted by husbandry measures, statistically incorporated in animal density variables, or by being strongly correlated with other, more significant variables. Several of the variables that were found to be important for productivity are correlated with climate and weather and therefore foreseen to be altered in a climatic change perspective. Abstract in Swedish / Sammanfattning: Kopplingar mellan biotiska och geografiska karaktäristika av renskötselområden och renproduktivitet i Sverige Renskötseln i Sverige är en form av pastoralism som använder stora ytor till betesmark. Produktiviteten inom rennäringen i Sverige beror på ett stort antal faktorer som varierar geografiskt och över tid. Undersökningens mål var att hitta kombinationer av faktorer som karaktäriserar förutsättningarna för renskötsel inom de 51 samebyarna i Sverige. Detta genomfördes genom att koppla variationen i renproduktivitet med kombinationer av omgivningsvariabler på sameby- och årsbasis. Produktiviteten definierades genom beräknad hjordtillväxt, slaktkroppskvalitet och vikter på slaktkroppar. Produktivitetsvariablerna relaterades till omgivningsvariablerna genom multipel linjär regression och strukturerad ekvationsmodellering (SEM). Omgivningsvariablerna ansågs för denna undersöknings tidsperspektiv vara antingen stabila (t.ex. topografi, vegetation och infrastrukturer) eller varierande över tid (t.ex. säsongslängder, väderhändelser, störningar och slaktstrategier). De mest relevanta omgivningsvariablerna användes i en klusteranalys för att gruppera samebyarna enligt deras likheter i förutsättningar för renskötsel. Variationen i produktivitet var större mellan samebyar än mellan år inom samebyar. Olika omgivningsvariabler visade sig vara relevanta mellan samebyar och mellan år. Säsongslängd och djurtäthet var relevanta i båda skalorna (mellan samebyar och mellan år), medan faktorer såsom topografisk brutenhet, snöförhållanden, aktivitet av störande insekter, stödutfodring, kalvslaktsandel och kondition på föregående års slaktkroppar var relevanta i en av dem. Snöfall, skarebildning och beteskvalitet antogs vara relevanta men visade sig inte vara signifikant korrelerade med produktiviteten. Dessa faktorer kan dock ha motverkats genom renskötselåtgärder, blivit statistisk inkorporerade i rentäthetsvariabler eller varit korrelerade med andra mer relevanta variabler. Flera av de signifikanta omgivningsvariablerna är väder- och klimatrelaterade, vilka därför antas förändras i den pågående klimatförändringen.